A Survey on Fingerprint Recognition System - Bansal, Anchal; Arora, Shakti; Singh, Surjeet (International Journal of Computer Sciences and Engineering, 2025)
Fingerprint Matching is a prevailing biometric technique used for providing authentication. In Fingerprint recognition systems a raw image is scanned, then pre-processing is performed, features are extracted as vectors and stored in fingerprint databases. In this paper, a review of different features of fingerprint recognition systems is presented. A brief of different types of fingerprint patterns followed by minutiae based approach is given in this paper. The invariant and discriminatory information present in the fingerprint images are captured using fingerprint ridges known as minutiae. Pattern recognition based approach is also studied followed by wavelet based approaches. The challenges and issues relating to fingerprint recognition system are critically reviewed in this paper. A good quality, noise free image should be used as input in fingerprint recognition system to achieve high accuracy. Different fingerprint image enhancement techniques are also analyzed and discussed in this paper.